Galbanic Acid-Coated Fe3O4 Magnetic Nanoparticles with Enhanced Cytotoxicity to Prostate Cancer Cells - Mohtashami, Leila; Ghows, Narjes; Tayarani-Najaran, Zahra; Iranshahi, Mehrdad (Planta Medica, 2019)
Galbanic acid is a natural sesquiterpene coumarin compound with different biological activities, particularly cytotoxicity against LNCaP (an androgen-dependent prostate cancer cell line). Galbanic acid induces apoptosis in LNCaP via down-regulation of androgen receptor. However, the poor water-solubility of galbanic acid limits further in vitro and in vivo studies. In this study we present the synthesis of galbanic acid-coated Fe3O4 magnetic nanoparticles and their cytotoxicity evaluation on three prostate cancer cell lines, including PC3 (an androgen-independent cell line), LNCaP, and DU145 (an androgen-independent cell line). The synthesized nanoparticles were characterized by X-ray diffraction spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, scattering electron microscopy, energy-dispersive X-ray spectroscopy, dynamic light scattering, and vibrating sample magnetometry. Our cytotoxicity evaluation demonstrated that galbanic acid was cytotoxic only against LNCaP cells, while the galbanic acid-coated Fe3O4 nanoparticles showed cytotoxicity on all tested cells, including androgen-dependent and -independent cell lines. This indicates that other mechanisms are involved in the cytotoxicity of galbanic acid in addition to androgen receptor down-regulation. In conclusion, the loading of galbanic acid on the surface of Fe3O4 magnetic nanoparticles turned out to be a successful approach to enhance the solubility and cytotoxicity of this compound.
Keywords: Ferula assa-foetida; Apiaceae; galbanic acid; prostate cancer; Fe3O4 magnetic nanoparticles; cytotoxicity